Reducing The Costs of Producing Individual Composite Molds While Simultaneously Improving Their Quality - Hubert SKOWRONEK; Paweł KAROLCZAK (Communications of International Proceedings, 2025)
This article presents the process of producing composite molds in a small enterprise (
Keywords: manufacturing costs; economic factors; composites